Joint Power Control and Beamforming for Peer-to-Peer MIMO Relay Systems - Khandaker, Muhammad; Rong, Yue (IEEE, 2011)
In this paper, we consider an interference multiple-input multiple-output (MIMO) relay system where multiple source nodes communicate with their desired destination nodes with the aid of distributed relay nodes all equipped with multiple antennas. We aim at minimizing the total source and relay transmit power such that a minimum signal-to-interference-plus noise ratio (SINR) threshold is maintained at each receiver. An iterative joint power control and beamforming algorithm is developed to achieve this goal. The proposed algorithm exploits transmit-relay-receive beamforming technique to mitigate the interferences from the unintended sources in conjunction with transmit power control. Numerical simulations are performed to demonstrate the effectiveness of the proposed iterative algorithm.